Temperature and humidity control system for broiler chicken coops - Ramadiani Ramadiani; Eko Wiji Setio Budianto; Dharma Widada; Masayu Widiastuti; Muhammad Labib Jundillah (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Stress in chickens due to rising cage temperatures is a problem that is often faced by breeders, especially broiler breeders. Research with the title "temperature and humidity control system for broiler chicken coops", has formulated the research problem as follows; how to make an automatic control system to maintain the temperature and humidity of the ras broiler chicken coop to keep it stable using Arduino Uno ATMega328. In this tool it has been set, if the temperature is ≥ 30º C then the water pump will turn on, and the water pump will turn off when the temperature is ≤ 29º C. Based on the results in this study, the temperature and humidity control system succeeded in helping farmers keep the temperature of the ras broiler chicken coop remained stable, so that farmers' production can be increased. In addition, this system also helps efficiency in terms of time and labor, because this system works automatically.